2008
DOI: 10.1111/j.1460-2695.2008.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress intensity factors for slanted through‐wall cracks based on elastic finite element analyses

Abstract: A B S T R A C T Based on detailed 3-dimensional (3-D) elastic finite element (FE) analyses, the present paper provides stress intensity factors (SIFs) for plates with slanted through-wall crack (TWC) and cylinders with slanted circumferential TWC. Regarding loading conditions, axial tension was considered for the plates, whereas axial tension, global bending and internal pressure were considered for the cylinders. To cover a practical range, the geometric variables affecting the SIF were systematically varied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…In this context, several experimental and numerical works have been made to provide a guideline on crack shape developments for sub‐critical through‐wall crack growth for limited geometries (for instance, see Ref. [9]), and the authors recently proposed stress intensity factor and COD solutions for slanted through‐wall cracks in a plate and slanted circumferential through‐wall cracks in a cylinder by performing detailed 3D FE analyses 10 (for more references, see Ref. [10]).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several experimental and numerical works have been made to provide a guideline on crack shape developments for sub‐critical through‐wall crack growth for limited geometries (for instance, see Ref. [9]), and the authors recently proposed stress intensity factor and COD solutions for slanted through‐wall cracks in a plate and slanted circumferential through‐wall cracks in a cylinder by performing detailed 3D FE analyses 10 (for more references, see Ref. [10]).…”
Section: Introductionmentioning
confidence: 99%
“…This approach assumes that a surface crack grows into an idealized TWC which has the same area as the surface crack after wall penetration. However, the recent research demonstrated that the idealized transition from a surface to a TWC can significantly affect a leak rate calculation and may provide nonconservative results in terms of leak rate, especially for long surface cracks [15,16]. Since the existing solutions for K I and COD of nonidealized TWC are limited to a certain number of geometries, additional solutions should be developed.…”
Section: Methodsmentioning
confidence: 96%
“…However, through‐wall cracks may still be developed in tubular members in offshore structures, in connection with girth welds or other stress raisers . Knowledge of the stress intensity factor for circumferential through‐wall cracks is also required for the evaluation of leak‐before‐break behaviour, stress corrosion cracking, and crack stability for piping, eg, in nuclear power plants.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] However, Nomenclature: a, half crack length, measured along the mid-thickness of the cylinder; E, Young's modulus; E*, = E for plane stress conditions; or = E/(1-ѵ 2 ) for plane strain conditions; F I , dimensionless geometry factor for tensile (mode I) load; F I *, nodal estimate of dimensionless geometry factor for tensile (mode I) load; F II , dimensionless geometry factor for torsional (mode II) load; F II *, nodal estimate of dimensionless geometry factor for torsional (mode II) load; J, polar moment of inertia; K, stress intensity factor; K I , K II , mode I and II stress intensity factors; K I *, K II *, nodal estimate of mode I and II stress intensity factors; l 1 , length of quarter-point element; l 2 , length of transition element; l e , size of elements near the crack, beyond the local crack tip mesh; L, half length of cylinder; P, applied tensile force; r, distance between a node and the crack tip node, measured on the cylindrical surface with radius R m ; R, radial distance; R m , mean radius of cylinder; t, wall thickness of cylinder; T, applied torque; u x , nodal value of displacement component parallel to the crack; u y , nodal value of displacement component normal to the crack; θ, half crack angle; λ, shell parameter = [12(1-ѵ) 2 ] 1/4 a/(R m t) 1/2 ; ѵ, Poisson's ratio; σ 0 , remote (nominal) axial stress; σ yy , axial stress component; τ, shear stress; τ 0 , remote (nominal) mid-thickness shear stress through-wall cracks may still be developed in tubular members in offshore structures, in connection with girth welds 7 or other stress raisers. 8 Knowledge of the stress intensity factor for circumferential through-wall cracks is also required for the evaluation of leak-before-break behaviour, 9,10 stress corrosion cracking, and crack stability 11 for piping, eg, in nuclear power plants.…”
Section: Introductionmentioning
confidence: 99%